Nationalism in Europe, 1815 to the present : a reader - Woolf, S. J. (Stuart Joseph) (London ; New York : Routledge, 1996)
`A major addition to the current literature on the challenging topic of how national identities are moulded.' - Michela Biddiss, Department of History University of Reading.
Nationality / J.S. Mill -- What is a nation? / Ernest Renan -- The nation / Otto Bauer -- Nation, nationality, internationalism / Marcel Mauss -- National states and national minorities / C.A. Macartney -- The idea of nation / Federico Chabod -- Reflections on nationalism / John Breuilly -- Language and nationalism / Joshua Fishman -- Urban space and monuments in the 'nationalization of the masses' : the Italian case / Bruno Tobia -- When was Wales? / G.A. Williams.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Nationalism; Nationalism -- Europe; Nationalisme; Nationalisme -- Europe; nationalism; POLITICAL SCIENCE -- Political Ideologies -- Nationalism; Nationalism; Europe